2013
DOI: 10.1038/nrn3492
|View full text |Cite
|
Sign up to set email alerts
|

The contextual brain: implications for fear conditioning, extinction and psychopathology

Abstract: Contexts surround and imbue meaning to events; they are essential for recollecting the past, interpreting the present and anticipating the future. Indeed, the brain’s capacity to contextualize information permits enormous cognitive and behavioural flexibility. Studies of Pavlovian fear conditioning and extinction in rodents and humans suggest that a neural circuit including the hippocampus, amygdala and medial prefrontal cortex is involved in the learning and memory processes that enable context-dependent beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
1,309
4
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,338 publications
(1,366 citation statements)
references
References 127 publications
49
1,309
4
4
Order By: Relevance
“…Our findings that the pHPC is selectively involved in processing information about environmental cues for which there is a personal history of smoking are consistent with animal studies, in which inactivation of the analogous dorsal HPC has been shown to disrupt expression of psychostimulant CPP (Meyers et al, 2003(Meyers et al, , 2006 and CIR (Fuchs et al, 2005). These animal studies of learned reward are also consistent with human and animal fear conditioning studies, in which the dorsal HPC has been shown to have a central role in context effects (Alvarez et al, 2008;Bast et al, 2003;Maren et al, 2013;Marschner et al, 2008). Interestingly and in contrast with pHPC, aHPC exhibited greater signal in response to smoking, relative to nonsmoking, cues regardless of cue category.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings that the pHPC is selectively involved in processing information about environmental cues for which there is a personal history of smoking are consistent with animal studies, in which inactivation of the analogous dorsal HPC has been shown to disrupt expression of psychostimulant CPP (Meyers et al, 2003(Meyers et al, , 2006 and CIR (Fuchs et al, 2005). These animal studies of learned reward are also consistent with human and animal fear conditioning studies, in which the dorsal HPC has been shown to have a central role in context effects (Alvarez et al, 2008;Bast et al, 2003;Maren et al, 2013;Marschner et al, 2008). Interestingly and in contrast with pHPC, aHPC exhibited greater signal in response to smoking, relative to nonsmoking, cues regardless of cue category.…”
Section: Discussionsupporting
confidence: 78%
“…Given the observed behavioural effects of CSD, specific brain regions important in the circuitries of fear conditioning (AMYG, vHIPP (Maren et al, 2013)), avoid-escape learning (AMYG, mPFC (Moscarello and LeDoux, 2013)), specific learned helplessness (mPFC (Amat et al, 2005;Pryce et al, 2011)) and fatigue (DeLuca et al, 2009), were investigated in terms of CSD effects on transcriptome-level gene expression, with brains collected at day 17. Importantly, these same regions exhibit altered structure-function-molecular genetic changes in depression e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing and canonical pathway analysis were applied to conduct a hypothesis-free, transcriptome-level analysis of effects of CSD on gene expression in specific brain regions. The regions selected for study, ventral hippocampus, medial prefrontal cortex, and central and basolateral nuclei of amygdala, are fundamental to the neurocircuitries underlying the behaviours under study here (Amat et al, 2005;Maren et al, 2013;Moscarello and LeDoux, 2013) as well as the corresponding depression psychopathologies (Capuron et al, 2007;Disner et al, 2011;Mayberg, 2003;Price and Drevets, 2010;Savitz et al, 2013;Sibille et al, 2009;Strigo et al, 2008). 7…”
Section: Introductionmentioning
confidence: 99%
“…Now the current study provides some of the first evidence for the reversal of behavioural effects of stress-induced IDO1-KYN pathway activation. Given the importance of amygdala and hippocampus in fear conditioning (Duvarci and Pare, 2014;LeDoux, 2000;Maren et al, 2013;Wolff et al, 2014) and stress-related psychiatric disorders (Harmer, 2013;Phelps and LeDoux, 2005;Price and Drevets, 2010; 31 Sheline et al, 2001), it is noteworthy that amygdala and vHIPP, together with other brain regions, exhibited increased levels of kynurenines. In healthy humans, LPS induced increased amygdala reactivity to fearful faces (Inagaki et al, 2012).…”
Section: Integrating Current Findings With Existing Evidence For Kyn-mentioning
confidence: 99%